Transverse myelitis extended to disseminated encephalitis in systemic lupus erythematosus: Histological evidence for vasculitis. Issue 6 (1st November 2016) - Tono, Toshihiro; Nagai, Tatsuo; Hoshiyama, Takayuki; Sakuma, Yuko; Wada, Tatsuhiko; Tanaka, Sumiaki; Hirohata, Shunsei
Abstract : A 42-year-old woman was admitted due to systemic lupus erythematosus complicated with glomerulonephritis and pulmonary hypertension. During the treatment for these complications, she presented motor paresis and sensory loss caused by transverse myelitis. In spite of methyl prednisolone pulse therapy, she further developed acute confusional state due to disseminated encephalitis and fell into respiratory arrest. On laboratory examination, elevation of anti-NR2 antibodies in serum as well as in cerebrospinal fluid was noted. Although she recovered from the disseminated encephalitis after extensive treatment with high doses of corticosteroid and intravenous cyclophosphamide, she suddenly died of pulmonary hypertension. Autopsy findings confirmed the presence of liquefaction necrosis in the entire circumference of the whole spinal cord along with intimal hyperplasia and obliteration of the small arteries, accompanied by mononuclear cell infiltration and disruption of internal elastic lamina. It is therefore most likely that our patient developed longitudinal transverse myelitis through spinal cord vasculitis, which extended to brainstem and brain parenchyma, leading to the development of disseminated encephalitis.